-- www.eigenmath.org/moller-scattering-2.txt -- Verify momentum and Mandelstam formulas for Moller scattering. p = sqrt(E^2 - m^2) p1 = (E, 0, 0, p) p2 = (E, 0, 0, -p) p3 = (E, p expsin(theta) expcos(phi), p expsin(theta) expsin(phi), p expcos(theta)) p4 = (E, -p expsin(theta) expcos(phi), -p expsin(theta) expsin(phi), -p expcos(theta)) I = ((1,0,0,0),(0,1,0,0),(0,0,1,0),(0,0,0,1)) gmunu = ((1,0,0,0),(0,-1,0,0),(0,0,-1,0),(0,0,0,-1)) gamma0 = ((1,0,0,0),(0,1,0,0),(0,0,-1,0),(0,0,0,-1)) gamma1 = ((0,0,0,1),(0,0,1,0),(0,-1,0,0),(-1,0,0,0)) gamma2 = ((0,0,0,-i),(0,0,i,0),(0,i,0,0),(-i,0,0,0)) gamma3 = ((0,0,1,0),(0,0,0,-1),(-1,0,0,0),(0,1,0,0)) gamma = (gamma0,gamma1,gamma2,gamma3) gammaT = transpose(gamma) gammaL = transpose(dot(gmunu,gamma)) "computing probability density" pslash1 = dot(p1,gmunu,gamma) pslash2 = dot(p2,gmunu,gamma) pslash3 = dot(p3,gmunu,gamma) pslash4 = dot(p4,gmunu,gamma) X1 = pslash1 + m I X2 = pslash2 + m I X3 = pslash3 + m I X4 = pslash4 + m I T1 = contract(dot(X3,gammaT,X1,gammaT),1,4) T2 = contract(dot(X4,gammaL,X2,gammaL),1,4) f11 = contract(dot(T1,transpose(T2))) T = contract(dot(X3,gammaT,X1,gammaT,X4,gammaL,X2,gammaL),1,6) f12 = contract(contract(T,1,3)) T1 = contract(dot(X4,gammaT,X1,gammaT),1,4) T2 = contract(dot(X3,gammaL,X2,gammaL),1,4) f22 = contract(dot(T1,transpose(T2))) "checking momentum formulas (1=ok)" f11 == 32 dot(p1,gmunu,p2) dot(p3,gmunu,p4) + 32 dot(p1,gmunu,p4) dot(p2,gmunu,p3) - 32 m^2 dot(p1,gmunu,p3) - 32 m^2 dot(p2,gmunu,p4) + 64 m^4 f12 == -32 dot(p1,gmunu,p2) dot(p3,gmunu,p4) + 16 m^2 dot(p1,gmunu,p2) + 16 m^2 dot(p1,gmunu,p3) + 16 m^2 dot(p1,gmunu,p4) + 16 m^2 dot(p2,gmunu,p3) + 16 m^2 dot(p2,gmunu,p4) + 16 m^2 dot(p3,gmunu,p4) - 32 m^4 f22 == 32 dot(p1,gmunu,p2) dot(p3,gmunu,p4) + 32 dot(p1,gmunu,p3) dot(p2,gmunu,p4) - 32 m^2 dot(p1,gmunu,p4) - 32 m^2 dot(p2,gmunu,p3) + 64 m^4 "checking Mandelstam formulas (1=ok)" s = dot(p1 + p2,gmunu,p1 + p2) t = dot(p1 - p3,gmunu,p1 - p3) u = dot(p1 - p4,gmunu,p1 - p4) f11 == 8 s^2 + 8 u^2 - 64 s m^2 - 64 u m^2 + 192 m^4 f12 == -8 s^2 + 64 s m^2 - 96 m^4 f22 == 8 s^2 + 8 t^2 - 64 s m^2 - 64 t m^2 + 192 m^4 m = 0 s == 4 E^2 t == -2 E^2 (1 - expcos(theta)) u == -2 E^2 (1 + expcos(theta)) t == -4 E^2 expsin(theta/2)^2 u == -4 E^2 expcos(theta/2)^2 (s^2 + u^2) expsin(theta/2)^4 == (1 + expcos(theta/2)^4) t^2 2 s^2 expsin(theta)^2 == 8 t u (s^2 + t^2) expcos(theta/2)^4 == (1 + expsin(theta/2)^4) u^2